2019
DOI: 10.1016/j.joco.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography angiography image quality assessment at varying retinal expertise levels

Abstract: Purpose To compare optical coherence tomography angiography (OCT-A) image quality gradings performed by readers of varying retinal expertise levels in different retinal diseases. Methods Central 3 × 3 mm 2 OCT-A images (AngioVue, Optovue) of 57 healthy controls (50.9 ± 22.4 years) and 148 patients (66.5 ± 14.1 years) affected by various chorioretinal diseases were retrospectively analyzed including early age-related macular degeneration (AMD, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
(33 reference statements)
0
8
1
Order By: Relevance
“…Despite comparable results concerning the total frequency of motion artifacts in both groups, it is noteworthy, that motion artifacts were also clearly higher in our control group compared to the literature 18,22,27 . One possible explanation could be the experience of the user who took the OCTA images.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…Despite comparable results concerning the total frequency of motion artifacts in both groups, it is noteworthy, that motion artifacts were also clearly higher in our control group compared to the literature 18,22,27 . One possible explanation could be the experience of the user who took the OCTA images.…”
Section: Discussioncontrasting
confidence: 85%
“…We assume that at most centers, clinical practice is that OCT and OCTA images are not taken by ophthalmologists, but by properly trained non-medical staff. Woetzel et al discussed the influence of different expertise levels in OCTA image quality assessment 22 . They concluded that trained non-ophthalmologic assessors could perform OCTA image quality assessment in a sufficient manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, scans with increased pathology are more likely to have disagreement between graders. 25 Additionally, as none of the factors studied was modifiable, the study was unable to identify additional ways to improve scan quality.…”
Section: Discussionmentioning
confidence: 98%
“…The quality of OCTA images is crucial for the accurate interpretation of morphological changes in the retinal vasculature and also affects the quantitative analysis results; therefore, improvement of image quality has become a hot research topic [6,7]. Several protocols have been used to evaluate the image quality of OCTA, including objective evaluations, such as single strength, contrast-to-noise ratio (CNR), and peak signal-to-noise ratio (PSNR), and subjective retinal expert evaluation [8][9][10][11]. Of these, the PSNR is one of the most outstanding and widely used objective parameter of image quality evaluation between different images [11,12].…”
Section: Introductionmentioning
confidence: 99%